Deixis in The Novel Fathers and Sons by Ivan Turgenev And Relevance to English Language Learning - Ferlina Putri Kinanti Wandani; Rochmat Budi Santoso; Giyoto Giyoto; Nestiani Hutami (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study investigates the forms of deixis found in the novel Fathers and Sons by Ivan Turgenev and examines their relevance to English language learning among junior high school students. The primary aim is to identify and describe the various deixis forms present in the novel and explore their potential application in the context of English language education within the framework of the Independent Curriculum. Employing a descriptive qualitative methodology, the research utilizes data documentation techniques by reading the novel and noting relevant dialogues. The data were collected through purposive sampling, resulting in the identification of 12 deixis forms in the novel Fathers and Sons by Ivan Turgenev. The findings highlight the diversity of deixis expressions used in the novel, which can serve as valuable linguistic resources for enhancing students’ understanding of deictic terms and their contextual usage in English. This research contributes to the development of teaching materials and strategies that incorporate authentic literary sources to improve language proficiency and pragmatic competence in junior high school learners.